2021
DOI: 10.1007/s40200-021-00760-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spirulina on type 2 diabetes: a systematic review and meta-analysis

Abstract: This document is the author's post-print version, incorporating any revisions agreed during the peer-review process. Some differences between the published version and this version may remain and you are advised to consult the published version if you wish to cite from it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 62 publications
1
16
0
1
Order By: Relevance
“…So much so that Spirulina supplements are widely available in powder or tablet form, the latter of which doses per tablet generally range from 200 mg to 1000 mg-500 mg appears to be the most common dose per tablet (27)(28)(29)(30)(31). Therapeutic dosing regimens of Spirulina varies from 0.8-10 g/d for 2 weeks to 6 months according to meta-analyses of randomized clinical trials (32)(33)(34)(35)(36)(37)(38)(39)(40), thus macronutrients and micronutrients across common Spirulina intake are not expressive as disseminated.…”
Section: Discussionmentioning
confidence: 99%
“…So much so that Spirulina supplements are widely available in powder or tablet form, the latter of which doses per tablet generally range from 200 mg to 1000 mg-500 mg appears to be the most common dose per tablet (27)(28)(29)(30)(31). Therapeutic dosing regimens of Spirulina varies from 0.8-10 g/d for 2 weeks to 6 months according to meta-analyses of randomized clinical trials (32)(33)(34)(35)(36)(37)(38)(39)(40), thus macronutrients and micronutrients across common Spirulina intake are not expressive as disseminated.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, we showed in hamsters fed with a high-fat diet, that Spirulysat ® supplementation improves sphingolipids profile and protects from lipid accumulation in aorta, suggesting a protective effect against cardiovascular disease [ 23 ]. Using whole Arthrospira, several studies in humans [ 44 , 45 ] support the beneficial effects of Arthrospira in improving hyperlipidaemia and reducing risk factors for cardiovascular disease. Similarly, a meta-analysis, including twelve trials with a dose of Arthrospira ranging from 1 to 19 g/d over an intervention period of 2 to 48 weeks, reports a significant reduction in LDL-cholesterol, triglycerides and total cholesterol levels.…”
Section: Discussionmentioning
confidence: 99%
“…Spirulina is useful in various diseases like nutritional deficiencies (Vit A, iron), cardiac diseases, diabetes mellitus, dyslipidaemia, inflammatory and degenerative diseases, hepatocellular carcinoma and breast cancer [31,32]. Some recent systematic reviews reported the beneficial effects of spirulina supplementations on plasma lipid concentration [33], obesity [34], human health [13], glycaemic control and serum lipoproteins [14,15]. In dentistry, apart from its use in OSF, it has been tried in treatment of periodontitis (topically in gel form) [35], reducing dental plaque and gingivitis (topical as 0.5% mouthwash) [36] and in oral mucosal lesions like leukoplakia [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Its therapeutic role in health and disease have been evaluated in many conditions (diabetes, hypertension, arthritis etc.) with beneficial results [13][14][15]. With its well-established antioxidant and anti-inflammatory potentials [16][17][18], its use in OSF has also been evaluated by various studies.…”
Section: Introductionmentioning
confidence: 99%